2020
DOI: 10.1016/j.jss.2019.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Observational Tools That Quantify Nontechnical Skills in the Operating Room: A Systematic Review

Abstract: a b s t r a c tBackground: Errors and adverse events in the operating room (OR) are associated with not only poor technical performance but also deficits in nontechnical skills (NTSs). Numerous tools have been developed to assess NTS in the OR. Our aim was to conduct a systematic review of observational tools and report on their implementation and psychometric properties to guide healthcare professionals, educators, and researchers in tool selection and use.Methods: A systematic literature search (January 1, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 104 publications
(255 reference statements)
0
12
0
1
Order By: Relevance
“…Two researchers independently reviewed the titles and abstracts against the inclusion and exclusion criteria. One researcher (JC) reviewed all articles twice, and another (DY) reviewed a random 10% of articles following previous published protocol (McMullan et al, 2020). Full-text articles were downloaded and assessed for eligibility if the inclusion of an article could not be determined from the initial screening.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two researchers independently reviewed the titles and abstracts against the inclusion and exclusion criteria. One researcher (JC) reviewed all articles twice, and another (DY) reviewed a random 10% of articles following previous published protocol (McMullan et al, 2020). Full-text articles were downloaded and assessed for eligibility if the inclusion of an article could not be determined from the initial screening.…”
Section: Methodsmentioning
confidence: 99%
“…Centered around NTS constructs, many role- and specialty-specific assessment tools have been developed to evaluate NTS behavior. A recent review identified 31 observational NTS tools for the OR (McMullan et al, 2020), which included evaluation ranging from that of the entire team (e.g., Observational Teamwork Assessment for Surgery [OTAS]) down to the individual surgical team member such as the attending surgeon (e.g., Nontechnical Skills for Surgeons [NOTSS] and Oxford Nontechnical Skills [NOTECHS]), anesthesiologist (e.g., Anesthetists’ Nontechnical Skills [ANTS]), and scrub nurse (Scrub Practitioner’s List of Intraoperative Nontechnical Skills [SPLINTS]; Fletcher et al, 2003; Mitchell et al, 2012; Robertson et al, 2014; Undre et al, 2007; Yule et al, 2008). These behavior rating systems have been used for NTS assessment primarily through expert observation in the OR.…”
Section: Introductionmentioning
confidence: 99%
“…might suspect that different scores could have been observed with different scales. 40,41 One might acknowledge that even if the two nontechnical skills scales are somewhat different, they are partly composed of elements that could be measuring the same behavior and would be "double counted" in their presence or absence. This choice may have influenced the overall performance score.…”
Section: Educationmentioning
confidence: 99%
“…The result of the consensus process is a validated set of RAS-critical behaviours. It comprises teamwork behaviours that are assessable, tangible and can be utilized for training, simulation, and teamwork improvement measures [13,[49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%